Nanocrystals from Oriented-Attachment for Energy Applications - He, Weidong (SpringerBriefs in Energy,, 2018)
This brief provides a comprehensive overview of contemporary research and materials technologies utilizing oriented-attachment nanocrystals (OA NCs) for the energy conversion devices. Starting with a historical introduction, the book presents basic theory with an emphasis on thermodynamic and kinetic models of the oriented-attachment nanocrystals growth. Further chapters review recent advances in the synthesis, characterization, and application of the oriented-attachment nanocrystals in fuel cells, batteries, supercapacitors, solar cells and photocatalysis. This book will appeal to researchers and scholars from a variety of disciplines including electrochemistry, materials science, chemical engineering, physics and mechanical engineering.